Effects of plyometric training on physical fitness in adolescent and adult female team sport athletes: a systematic review and meta-analysis - Lin, Gesheng; Zhang, Ruli; Wu, Kai; Deng, Beiwang; Shi, Yuer; Huang, Wenwei; He, Jiaxin; Sun, Jian (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to investigate the effects of plyometric training (PT) on various physical fitness outcomes in adolescent and adult female team sport athletes.MethodsA systematic literature search was conducted across four electronic databases from inception to April 2025. Data analyses were performed using the meta and metafor packages in R version 4.4.3.ResultsA total of 20 studies were included, involving 175 soccer players, 141 basketball players, 103 handball players, and 77 volleyball players. Compared with control groups, PT significantly improved countermovement jump (CMJ) height (ES: adolescents = 0.89; adults = 0.54) and change-of-direction (COD) performance (ES: adolescents = −1.42; adults = −0.86) in both adolescent and adult female athletes. However, significant improvement in 20-m sprint performance was observed only in adolescents (ES: adolescents = −0.99; adults = −0.32). Subgroup analyses showed that, compared to lower training accumulation, adolescents exhibited significantly greater improvements in CMJ height when the training duration was ≥9 weeks or the total sessions were ≥16. For COD performance, significantly greater improvements were observed when the training duration was ≥9 weeks, the total sessions were ≥18, and the total ground contacts were ≥1260.ConclusionPT can significantly improve CMJ height and COD performance in both adolescent and adult female athletes, and significantly enhance sprint performance in adolescents. Compared to adults, adolescents demonstrate greater responsiveness to PT and are more sensitive to training accumulation.Systematic Review Registrationidentifier CRD420251041817.